Chaoborus and Gasterosteus Anti-Predator Responses in Daphnia pulex Are Mediated by Independent Cholinergic and Gabaergic Neuronal Signals - Weiss, Linda C. (Public Library of Science, 2012)
Many prey species evolved inducible defense strategies that protect effectively against predation threats. Especially the crustacean Daphnia emerged as a model system for studying the ecology and evolution of inducible defenses. Daphnia pulex e.g. shows different phenotypic adaptations against vertebrate and invertebrate predators. In response to the invertebrate phantom midge larvae Chaoborus (Diptera) D. pulex develops defensive morphological defenses (neckteeth). Cues originating from predatory fish result in life history changes in which resources are allocated from somatic growth to reproduction. While there are hints that responses against Chaoborus cues are transmitted involving cholinergic neuronal pathways, nothing is known about the neurophysiology underlying the transmission of fish related cues. We investigated the neurophysiological basis underlying the activation of inducible defenses in D. pulex using induction assays with the invertebrate predator Chaoborus and the three-spined stickleback Gasterosteus aculeatus. Predator-specific cues were combined with neuro-effective substances that stimulated or inhibited the cholinergic and gabaergic nervous system. We show that cholinergic-dependent pathways are involved in the perception and transmission of Chaoborus cues, while GABA was not involved. Thus, the cholinergic nervous system independently mediates the development of morphological defenses in response to Chaoborus cues. In contrast, only the inhibitory effect of GABA significantly influence fish-induced life history changes, while the application of cholinergic stimulants had no effect in combination with fish related cues. Our results show that cholinergic stimulation mediates signal transmission of Chaoborus cues leading to morphological defenses. Fish cues, which are responsible for predator-specific life history adaptations involve gabaergic control. Our study shows that both pathways are independent and thus potentially allow for adjustment of responses to variable predation regimes.